If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 80x + 55 = 7 Reorder the terms: 55 + 80x = 7 Solving 55 + 80x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-55' to each side of the equation. 55 + -55 + 80x = 7 + -55 Combine like terms: 55 + -55 = 0 0 + 80x = 7 + -55 80x = 7 + -55 Combine like terms: 7 + -55 = -48 80x = -48 Divide each side by '80'. x = -0.6 Simplifying x = -0.6
| (9u+2)(6u+1)=0 | | 20x=240+12x-360 | | (T-7)(6t-7)=0 | | -6(1+r)-8r=92 | | 2(3x+4)=5(x-1)+x+13 | | 2x+9=2x+22 | | J=z-a/x | | 5t+4=1t-2 | | J(8j-7)=0 | | -3x+-6= | | 6(2a+10)=5a+5 | | 21-2x=43-5x | | 6d-2= | | (x)/(2)-1=2-x | | ×/3=11 | | (-4.3)-z=11 | | 2x+2=4+6x-54 | | 47-7x=5x-20 | | (S+5)(8s+9)=0 | | 7.9x-17.9=29.5 | | -12(x+4)=-3(x+6)+x-30 | | 0.5(4x-1)=4(3+x) | | 2a+28=4a-4 | | 144-5x=171-8x | | 3(x+3)-10=32 | | 6x+5+3x=136 | | 12-x=36 | | (7n-3)(6n-7)=0 | | h=(-16)t^2+800(t)+125 | | sin(5t)-cos(5t)=0 | | 6a-5= | | (8z-1)(z+3)=0 |